Foreign Language Anxiety in Arabic Speaking: The Mediating Role of Cognitive Interference and Fear of Negative Evaluation - Halimahtus Sa'Diah; Ari Khairurrijal Fahmi (Jurnal Internasional Pendidikan Bahasa Arab, 2026)
Foreign language anxiety deeply affects oral fluency, creating a significant gap between students' theoretical knowledge and communicative skills. This qualitative descriptive study examines the dynamic interaction between emotional and cognitive factors underlying Arabic speaking anxiety to understand how it subjectively interferes with oral performance. Data were collected through in-depth semi-structured interviews and classroom observations, and analyzed systematically using the Miles and Huberman interactive model. The findings reveal that the fear of negative evaluation emerges as the most dominant source of anxiety, reaching an average of 70%. This emotional burden triggers cognitive overload and compromised attentional control, resulting in sudden mental blocking, severe vocabulary retrieval difficulties, and reduced fluency due to working memory disruption. Critically, these performance breakdowns stem from affective interference rather than an actual deficit in linguistic competence. The study offers a novel conceptual by linking this dominant anxiety to the unique cultural and religious background of Indonesian students, who perceive Arabic as a sacred language, thereby inflating their internal perfectionism and fear of social judgment. This study concludes that pedagogical interventions must shift toward structured, low-stakes speaking environments, explicitly recommending procedural scaffolding such as the Think-Pair-Share activity and somatic grounding exercises.